Betty and Veronica friends forever - Golliher, Bill (Archie Comic Publications, Inc., 2019)
Classic Betty and Veronica stories are back with this collection of tales that see the two iconic BFFs travel the world and get into all kinds of international adventures!
"Archie characters created by John L. Goldwater; the likenesses of the original Archie characters were created by Bob Montana"--Preliminary page
Keywords: Jugend; Freundschaft; Mädchen; Comic